Development of Interactive Physics E-Module Using the SETS (Science, Environment, Technology, Society) Approach to Improve Science Literacy Dimension of Content and Process Dimensions in Fluid Dynamics Material - Syafutri, Eka; Widodo, Widodo; Pramudya, Yudhiakto (Indonesian Review of Physics (IRiP), 2020)
This development research produces interactive physic electronic products using the interactive physics SETS approach (Science, Environment, Technology and Society) in terms of presenting the components of illustration, language, and the suitability of the material. The validity results of the electronic module carried by experts and teachers develeop the average yield of 96.36% so it is feasible to use. The study design is pretest-posttest control group to see the improvement ofÂ  literacy dimension process. Subject of the study consisted of two groups: the experimental group and the control group. The data collection formed by science literacy of dimension content and process is analyzed using MANOVA with significance level of 5%. The results showed that the electronic module using SETS approach significantly influence the improvement of science literacy dimension content and process.